TPU / CNT (at) PDA / AgNWs foam strain sensor and preparation method thereof

By adopting the preparation method of TPU/CNT@PDA/AgNWs foam strain sensor in flexible strain sensors, the trade-off problem between sensor sensitivity and detection range is solved, and the stability is maintained when temperature changes, achieving sensor performance with high durability and hysteresis.

CN119860707APending Publication Date: 2025-04-22BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510043715.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

There is a trade-off between sensitivity and detection range of existing flexible strain sensors, making it difficult to achieve high sensitivity and wide detection range at the same time, and traditional strain sensors exhibit negative temperature coefficient effects when ambient temperature changes, resulting in decreased sensitivity and signal distortion.

Method used

The preparation method of TPU/CNT@PDA/AgNWs foam strain sensor is adopted, and the durability and hysteresis of the sensor are improved and its stability in humid environment is enhanced through PDA modification of TPU/CNT composite foam and impregnation loading.

Benefits of technology

It realizes the high durability and hysteresis of the piezoresistive strain sensor, enhances its stability and anti-interference ability under variable environmental conditions, and is suitable for high-demand occasions such as human movement, gesture recognition and emergency signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119860707A_ABST
    Figure CN119860707A_ABST
Patent Text Reader

Abstract

The invention discloses a TPU / CNT (at) PDA / AgNWs foam strain sensor and a preparation method thereof. The preparation method comprises the following steps: step 1, preparing TPU / CNT composite foam; step 2, preparation of an AgNWs dispersion liquid; step 3, preparing a TPU / CNT (at) PDA / AgNWs foam strain sensor; step 3.1, PDA modification of the TPU / CNT foam is carried out; and step 3.2, dipping and loading of the AgNWs. According to the TPU / CNT (at) PDA / AgNWs strain sensor, the durability and hysteresis of the strain sensor are improved. The invention also discloses a preparation method of the TPU / CNT (at) PDA / AgNWs strain sensor. According to the foam strain sensor prepared by the invention, the sensitivity, the detection range and the long-term stability of the sensor are remarkably improved, and the foam strain sensor has remarkable advantages in the aspects of the sensitivity, the reliability and the environmental adaptability of the strain sensor, can be used as wearable equipment and can also be applied to human body thermal management.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flexible sensors, and in particular to a thermoplastic polyurethane (TPU), carboxylated multi-walled carbon nanotubes (CNT), polydopamine (PDA) and silver nanowires (AgNWs) foam strain sensor; and also to a preparation method of the TPU / CNT@PDA / AgNWs foam strain sensor. Background Art

[0002] Flexible strain sensors have broad application potential in wearable devices, health monitoring, intelligent robots and other fields. However, most flexible sensors currently have an obvious trade-off between sensitivity and detection range, and it is difficult to achieve both high sensitivity and wide detection range. This limitation significantly restricts the further development and practical application of flexible sensors.

[0003] Conductive composite materials are the core materials of flexible strain sensors, with good flexibility and conductivity. However, many composite materials have poor strain sensitivity and resistance strain stability due to insufficient interface bonding or easy breakage of the conductive network. Improving the performance of sensors by optimizing the surface structure and internal conductive network of composite materials remains an important challenge.

[0004] Flexible strain sensors are affected by changes in ambient temperature in practical applications. Traditional strain sensors usually exhibit a negative temperature coefficient effect, resulting in decreased sensitivity and signal distortion. Therefore, developing flexible strain sensors with a positive temperature coefficient effect and improving their durability has become one of the research hotspots. Summary of the invention

[0005] The first object of the present invention is to provide a method for preparing a TPU / CNT@PDA / AgNWs foam strain sensor, which improves the durability and hysteresis of the piezoresistive strain sensor.

[0006] The second object of the present invention is to provide a TPU / CNT@PDA / AgNWs foam strain sensor that can be used as a flexible strain sensor with high durability and hysteresis.

[0007] The first technical solution adopted by the present invention is a method for preparing a TPU / CNT@PDA / AgNWs foam strain sensor, comprising the following steps:

[0008] Step 1, preparing TPU / CNT composite foam;

[0009] Step 2, preparation of AgNWs dispersion;

[0010] Step 3, preparation of TPU / CNT@PDA / AgNWs foam strain sensor;

[0011] Step 3.1, PDA modification of TPU / CNT foam;

[0012] Step 3.2, dip-loading of AgNWs.

[0013] Further, step 1 is to prepare TPU / CNT composite foam, and the specific steps are as follows: dissolving TPU particles in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 20-30%, stirring at 50-60° C. for 12-24 hours to ensure that the TPU / DMF solution is uniform; gradually adding 1-3% carboxylated carbon nanotube CNT powder to the above solution, and continuing to stir at 50-60° C. for 12-24 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; and adding the mixed solution to the mixture. NaCl particles are added as a template, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 20-80%; the mixed solution is poured into a glass culture dish, and dried in an oven at 70-90° C. overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water, and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain TPU / CNT composite foam.

[0014] Further, the steps of preparing the AgNWs dispersion in step 2 are as follows: first, 10-20 mL of ethylene glycol (EG) and 7-14 mg of copper chloride dihydrate (CuCl 2 ·2H 2 O) to prepare a solution; prepare two beakers containing 30-60mL EG, add 942-1884mg polyvinyl pyrrolidone (PVP) to one beaker and 479-958mg silver nitrate (AgNO 3 All solutions were ultrasonically treated in a 20-30°C water bath until completely dissolved; then 100-200 mL of EG solution was placed in a 500 mL three-necked flask and refluxed at 150-170°C for 1.5-3 hours; then 800-1600 μL of CuCl dissolved by ultrasonication was added. 2 ·2H 2 O solution was slowly added to the reaction system, and the addition process lasted for about 10-20 minutes; then, 30-60 mL of PVP solution was gradually added; after the above reaction was completed, AgNO 3-EG solution was added to the reaction system in stages, and the addition time was controlled within 15-20 minutes; the reaction temperature was maintained at 150-170°C, and the reaction was continued for 2-4 hours; after the reaction, the solution was cooled to room temperature, and 3-5 volumes of acetone were added to complete precipitation; the final product was washed with acetone and anhydrous ethanol 3-5 times, and centrifuged at 5000-7000rpm for 5-10 minutes to remove residual impurities; the product was dispersed in deionized water and prepared into a AgNWs solution with a concentration of 2-4 mg / mL.

[0015] Furthermore, the preparation and treatment steps of the PDA modification of the TPU / CNT foam in step 3.1 are as follows: prepare 10-20mMTris-HCl buffer (pH 8.5) and dissolve dopamine to prepare a dopamine solution; immerse the TPU / CNT foam obtained in step 1 in the dopamine solution and stir the reaction at room temperature for 12-24 hours to achieve uniform polymerization of surface dopamine; after the reaction is completed, rinse the foam with deionized water to remove unpolymerized dopamine monomers; place the dopamine-modified foam in a vacuum drying oven and dry it at 50-70°C for 12-24 hours to ensure the stable formation of the surface dopamine film to finally obtain a PDA-modified TPU / CNT composite material.

[0016] Furthermore, step 3.2, the preparation and processing steps for the immersion loading of AgNWs are as follows: immerse the TPU / CNT@PDA composite material obtained in step 3.1 into the AgNWs dispersion (concentration of 2-4 mg / mL) obtained in step 2, and gently stir for 30-60 minutes at room temperature to allow the AgNWs to evenly adhere to the foam surface; and repeatedly immerse the AgNWs-impregnated TPU / CNT@PDA foam into the AgNWs dispersion, record the load of AgNWs, and obtain the TPU / CNT@PDA composite material; connect copper foil electrodes at both ends of the TPU / CNT@PDA composite material, and the upper and lower surfaces of the TPU / CNT@PDA composite material are respectively encapsulated with PI (polyimide) film, and then lead out wires from the copper foil electrodes at both ends to assemble the TPU / CNT@PDA / AgNWs foam strain sensor.

[0017] The second technical solution adopted by the present invention is a TPU / CNT@PDA / AgNWs foam strain sensor prepared by the above method.

[0018] The beneficial effects of the present invention are:

[0019] (1) The method of the present invention successfully prepared carboxylated carbon nanotubes (MWCNT) / thermoplastic polyurethane (TPU). The second purpose is to add PDA as an adhesive to the TPU / CNT composite material and add AgNWs to prepare thermoplastic polyurethane / carboxylated carbon nanotubes@polydopamine / silver nanowires (TPU / CNT@PDA / AgNWs) which can be used as a flexible strain sensor. This method improves the durability and hysteresis of the piezoresistive strain sensor.

[0020] (2) The present invention adopts a method combining NaCl salt template sacrificial method and impregnation to design a thermoplastic polyurethane flexible foam pull-up sensor. Carboxylated carbon nanotubes are blended in the foam, and the polydopamine solution is attached to the surface of the TPU / CNT foam by impregnation, thereby enhancing the adhesion between the TPU / CNT foam and the silver nanowires. In addition, the TPU / CNT composite foam is immersed in the silver nanowire solution, and the nanosilver wires are adsorbed on the thermoplastic polyurethane / carboxylated carbon nanotube composite material, thereby improving and increasing the conductivity of the TPU / CNT composite material.

[0021] (3) The composite foam prepared by the present invention exhibits good conductivity retention characteristics during long-term use, and can maintain stable resistance changes even under large tensile deformation. The present invention not only effectively improves the surface activity and adhesion of the composite material, but also enhances its stability in a humid environment. This enables the sensor to work reliably under variable environmental conditions and has strong anti-interference capabilities, and is particularly suitable for high-demand occasions such as human motion, gesture recognition, and emergency signal transmission. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The surface morphology of TPU / CNT under the condition of a scale of 200 μm in Example 1 of the present invention;

[0023] Figure 2 The surface morphology of the TPU / CNT@PDA composite material under the condition of a scale of 200 μm in Example 1 of the present invention;

[0024] Figure 3 The surface morphology of the TPU / CNT@PDA / AgNWs composite material under the condition of a scale of 200 μm in Example 1 of the present invention;

[0025] Figure 4 The surface morphology of the TPU / CNT@PDA / AgNWs composite material under the condition of a scale of 5 μm in Example 1 of the present invention;

[0026] Figure 5The Raman spectra of the TPU / CNT, TPU / CNT@PDA and TPU / CNT@PDA / AgNWs composite materials in Example 1 of the present invention;

[0027] Figure 6 FTIR images of TPU / CNT, TPU / CNT@PDA and TPU / CNT@PDA / AgNWs composite foams in Example 1 of the present invention;

[0028] Figure 7 This is the XPS full spectrum scan of TPU / CNT, TPU / CNT@PDA and TPU / CNT@PDA / AgNWs composite foam in Example 1 of the present invention

[0029] Figure 8 This is the C1s fine spectrum analysis of the TPU / CNT material in Example 1 of the present invention;

[0030] Fig. 9 This is the C1s fine spectrum analysis of the TPU / CNT@PDA / AgNWs material in Example 1 of the present invention;

[0031] Fig.10 The stress-strain curves of TPU / CNT, TPU / CNT@PDA and TPU / CNT@PDA / AgNWs materials in Example 1 of the present invention;

[0032] Fig.11 This is a physical picture of the TPU / CNT@PDA / AgNWs strain sensor in Example 1 of the present invention;

[0033] Fig.12 This is the relative resistance change of the TPU / CNT@PDA / AgNWs material under stretching in Example 1 of the present invention.

[0034] Fig.13 is the response time of the TPU / CNT@PDA / AgNWs strain sensor in Example 1 of the present invention

[0035] Fig.14 is the recovery time of the TPU / CNT@PDA / AgNWs strain sensor in Example 1 of the present invention

[0036] Fig.15 The relative resistance change of the sensor under cyclic stretching and release at 5-40% strain in Example 1 of the present invention is

[0037] Fig.16 This is a durability test of the TPU / CNT@PDA / AgNWs strain sensor in Example 1 of the present invention under 20% tension.

[0038] Fig.17 It is the normalized relative resistance change of the TPU / CNT@PDA / AgNWs sensor from room temperature (20°C) to 100°C in Example 1 of the present invention.

[0039] Fig.18 It is the relative resistance response of the TPU / CNT@PDA / AgNWs sensor in Example 1 of the present invention when cyclically heating and cooling from 20°C to 70°C. DETAILED DESCRIPTION

[0040] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0041] The invention provides a method for preparing a TPU / CNT@PDA / AgNWs foam strain sensor, comprising the following steps:

[0042] Step 1, preparing TPU / CNT composite foam;

[0043] Step 1 is implemented according to the following steps:

[0044] The TPU particles are dissolved in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 20-30%, and the solution is stirred at 50-60° C. for 12-24 hours to ensure that the TPU / DMF solution is uniform; 1-3% (carboxylated carbon nanotube CNT powder is gradually added to the solution, and the solution is stirred at 50-60° C. for 12-24 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template agent, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 20-80%; the mixed solution is poured into a glass culture dish, and dried in an oven at 70-90° C. overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water, and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

[0045] The TPU particles are dissolved in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 20-30%, and the solution is stirred at 50-60° C. for 12-24 hours to ensure that the TPU / DMF solution is uniform; 1-3% (carboxylated carbon nanotube CNT powder is gradually added to the solution, and the solution is stirred at 50-60° C. for 12-24 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template agent, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 20-80%; the mixed solution is poured into a glass culture dish, and dried in an oven at 70-90° C. overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water, and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

[0046] Step 2, preparation of AgNWs dispersion;

[0047] Step 2 is implemented as follows:

[0048] First, 10-20 mL of ethylene glycol (EG) and 7-14 mg of copper chloride dihydrate (CuCl 2 ·2H 2 Prepare two beakers containing 30-60 mL EG, add 942-1884 mg polyvinyl pyrrolidone (PVP) to one beaker and 479-958 mg silver nitrate (AgNO 3 All solutions were ultrasonically treated in a 20-30°C water bath until completely dissolved; then 100-200 mL of EG solution was placed in a 500 mL three-necked flask and refluxed at 150-170°C for 1.5-3 hours; then 800-1600 μL of CuCl dissolved by ultrasonication was added. 2 ·2H 2 O solution was slowly added to the reaction system, and the addition process lasted for about 10-20 minutes; then, 30-60 mL of PVP solution was gradually added; after the above reaction was completed, AgNO 3 -EG solution was added to the reaction system in stages, and the addition time was controlled within 15-20 minutes; the reaction temperature was maintained at 150-170°C, and the reaction was continued for 2-4 hours; after the reaction, the solution was cooled to room temperature, and 3-5 volumes of acetone were added to complete precipitation; the final product was washed with acetone and anhydrous ethanol 3-5 times, and centrifuged at 5000-7000rpm for 5-10 minutes to remove residual impurities; the product was dispersed in deionized water and prepared into a AgNWs solution with a concentration of 2-4 mg / mL.

[0049] Step 3.1, PDA modification of TPU / CNT foam;

[0050] Step 3.1 is implemented as follows:

[0051] Prepare a dopamine solution by preparing a 10-20 mM Tris-HCl buffer (pH 8.5) and dissolving dopamine; immerse the TPU / CNT foam obtained in step 1 in the dopamine solution, and stir the reaction at room temperature for 12-24 hours to achieve uniform polymerization of surface dopamine; after the reaction is completed, rinse the foam with deionized water to remove unpolymerized dopamine monomers; place the dopamine-modified foam in a vacuum drying oven and dry it at 50-70° C. for 12-24 hours to ensure the stable formation of the surface dopamine film, and finally obtain a PDA-modified TPU / CNT composite material.

[0052] Step 3.2, dip-loading of AgNWs.

[0053] Step 3.2 is implemented as follows:

[0054] The TPU / CNT@PDA composite material obtained in step 3.1 is immersed in the AgNWs dispersion (concentration of 2-4 mg / mL) obtained in step 2, and gently stirred for 30-60 minutes at room temperature to allow the AgNWs to evenly adhere to the foam surface; and the AgNWs-impregnated TPU / CNT@PDA foam is repeatedly immersed in the AgNWs dispersion, and the load of AgNWs is recorded to obtain the TPU / CNT@PDA composite material; copper foil electrodes are connected at both ends of the TPU / CNT@PDA composite material, and the upper and lower surfaces of the TPU / CNT@PDA composite material are respectively encapsulated with PI films, and then wires are led out from the copper foil electrodes at both ends to assemble the TPU / CNT@PDA / AgNWs foam strain sensor.

[0055] The present invention also provides a high-performance flexible strain sensor based on TPU / CNT@PDA / AgNWs composite foam, which is prepared by the above method.

[0056] Example 1

[0057] The TPU particles are dissolved in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 20%, and the solution is stirred at 50°C for 12 hours to ensure that the TPU / DMF solution is uniform; 1% (carboxylated carbon nanotube CNT powder is gradually added to the solution, and the solution is stirred at 50°C for 12 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template agent, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 20%; the mixed solution is poured into a glass culture dish and dried in an oven at 70°C overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

[0058] The TPU particles are dissolved in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 20%, and the solution is stirred at 50°C for 12 hours to ensure that the TPU / DMF solution is uniform; 1% (carboxylated carbon nanotube CNT powder is gradually added to the solution, and the solution is stirred at 50°C for 12 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template agent, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 20%; the mixed solution is poured into a glass culture dish and dried in an oven at 70°C overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

[0059] First, 10 mL of ethylene glycol (EG) and 7 mg of copper chloride dihydrate (CuCl 2 ·2H 2 Prepare two beakers containing 30 mL of EG, add 942 mg of polyvinyl pyrrolidone (PVP) to one beaker and 479 mg of silver nitrate (AgNO 3 All the solutions were ultrasonically treated in a 20°C water bath until completely dissolved; then 100 mL of EG solution was placed in a 500 mL three-necked flask and refluxed at 150°C for 1.5 hours; then 800 μL of CuCl dissolved by ultrasonication was added 2 ·2H 2 O solution was slowly added dropwise to the reaction system for about 10 minutes; then, 30 mL of PVP solution was gradually added; after the above reaction was completed, AgNO 3-EG solution was added to the reaction system in stages, and the addition time was controlled within 15 minutes; the reaction temperature was maintained at 150°C, and the reaction was continued for 2 hours; after the reaction, the solution was cooled to room temperature, and 3 volumes of acetone were added to complete the precipitation; the final product was washed 3 times with acetone and anhydrous ethanol, and centrifuged at 5000 rpm for 5 minutes to remove residual impurities; the product was dispersed in deionized water and prepared into a AgNWs solution with a concentration of 2 mg / mL.

[0060] Prepare a dopamine solution by preparing a 10 mM Tris-HCl buffer (pH 8.5) and dissolving dopamine; immerse the obtained TPU / CNT foam in the dopamine solution and stir the reaction at room temperature for 12 hours to achieve uniform polymerization of surface dopamine; after the reaction is completed, rinse the foam with deionized water to remove unpolymerized dopamine monomers; place the dopamine-modified foam in a vacuum drying oven and dry it at 50°C for 12 hours to ensure the stable formation of the surface dopamine film, and finally obtain a PDA-modified TPU / CNT composite material.

[0061] The obtained TPU / CNT@PDA composite material was immersed in AgNWs dispersion (concentration of 2 mg / mL) and gently stirred for 30 minutes at room temperature to allow AgNWs to evenly adhere to the foam surface; the AgNWs-impregnated TPU / CNT@PDA foam was repeatedly immersed in the AgNWs dispersion, and the load of AgNWs was recorded to obtain the TPU / CNT@PDA composite material; copper foil electrodes were connected at both ends of the TPU / CNT@PDA composite material, and the upper and lower surfaces of the TPU / CNT@PDA composite material were respectively encapsulated with PI film, and then wires were led out from the copper foil electrodes at both ends to assemble the TPU / CNT@PDA / AgNWs foam strain sensor.

[0062] In order to obtain the surface morphology of TPU / CNT, TPU / CNT@PDA and TPU / CNT@PDA / AgNWs composite foams prepared by NaCl salt template method, we used scanning electron microscopy to observe and photograph their surface morphology. Figure 1-4 As shown. Figure 1 As shown, the NaCl template process formed uniformly distributed pores. Figure 2 After PDA modification, the surface roughness of TPU / CNT foam was significantly improved, indicating that the PDA coating was deposited uniformly, enhancing the surface roughness and functionalization. Figure 3 It can be seen that the high aspect ratio AgNWs synthesized by the polyol method are uniformly distributed on the surface of TPU / CNT@PDA / AgNWs composite materials. Figure 4The high-magnification image in 5μm further shows that AgNWs are uniformly dispersed on the PDA-treated TPU / CNT surface without obvious aggregation. The uniform distribution contributes to the excellent conductivity and strain sensitivity of the composite foam, ensuring its high performance in various applications.

[0063] Figure 5 The Raman spectra of TPU / CNT composites and their foams are shown. For the TPU / CNT sample, the D band observed at 1346.5 cm-1 is attributed to defects and amorphous structure in CNTs, while the G band at 1610 cm-1 corresponds to sp 2 The in-plane stretching vibrations of the hybridized carbon atoms represent the ordered graphitic structure of the nanotubes. In addition, the presence of the G' band and the 2D band at 2697 and 2922.5 cm-1, respectively, further confirm the graphitic nature of the carbon nanotubes. It is worth noting that the intensity and contour characteristics of the 2D band indicate the multilayer structure of the CNTs. These characteristic Raman peaks confirm the successful incorporation of CNTs into the composite material. The graphitic structure and multilayer nature of the carbon nanotubes indicate that the composite material has excellent electrical properties and strain responsiveness, laying the foundation for its potential application in conductive and sensor devices.

[0064] FTIR spectroscopy is used to analyze the molecular structure of TPU / CNT and its composite foam, such as Figure 6 As shown. The FTIR spectrum shows several different absorption peaks at 3336, 2958, 1726, 1595 and 1525 cm-1. The broad absorption band at 3336 cm-1 can be attributed to the stretching vibration of NH or OH groups, indicating the presence of hydrogen bonding interactions in the composite material. The peak at 2958 cm-1 corresponds to the symmetric and asymmetric stretching vibrations of the CH bond, confirming the presence of aliphatic alkyl groups in the TPU matrix. The strong absorption peak at 1726 cm-1 is characteristic of the stretching vibration of the C=O carbonyl group, which comes from the ester group in the TPU molecular chain. The peak at 1525 cm-1 is attributed to the bending vibration of NH and the stretching vibration of CN, indicating the presence of polyurethane groups in TPU. In addition, the absorption peak at 1595 cm-1 corresponds to the aromatic C=C vibration in the carbon nanotubes. The presence of these characteristic absorption peaks not only confirms the chemical integrity of the TPU matrix, but also shows that the incorporation of CNTs does not significantly change the basic molecular structure of TPU, providing strong evidence for the interaction between molecules.

[0065] Figure 7-9Figure 2 shows the XPS spectra of TPU / CNT and TPU / CNT@PDA / AgNWs composite foams. The XPS spectrum of the TPU / CNT sample mainly shows the characteristic peaks of carbon (C 1s) and oxygen (O 1s), corresponding to the presence of the PU matrix and CNTs. In contrast, the TPU / CNT@PDA / AgNWs foam shows obvious silver (Ag 3d) peaks, such as Fig. 9 As shown, the peaks are located at 367.5 and 373.5 eV, which are attributed to the Ag 3d 5 / 2 and Ag 3d 3 / 2 The spin-orbit coupling of 2.5 N·m2 indicates the presence of metallic silver. Figure 8 High-resolution C1s XPS spectra of the two samples are shown. The TPU / CNT sample mainly exhibits characteristic peaks corresponding to CC / CH (284.8 eV), CO (286.2 eV), and C=O (288.6 eV), which are consistent with the characteristic peaks of the PU matrix and CNTs. In the TPU / CNT@PDA / AgNWs sample, in addition to these peaks, an obvious CN peak was observed at 285.5 eV, indicating the successful incorporation of PDA. The CN peak is attributed to the amine or imine groups in PDA, further confirming the significant modification of the surface chemical environment by the PDA coating. In addition, the enhanced C=O peak indicates that the presence of PDA and AgNWs induces the modification of surface functional groups.

[0066] Stress-strain curve ( Fig.10 ) shows that the TPU / CNT sensor has a lower modulus and higher elongation than the TPU / CNT@PDA / AgNWs composite foam, which can be attributed to its porous structure. Fig.11 As shown. Multiple measurements were performed to characterize the stress-strain properties of TPU / CNT, TPU / CNT@PDA, and TPU / CNT@PDA / AgNWs foams. A trend of increasing stress values ​​was observed with increasing material compositeness, while strain values ​​decreased. This property makes composite foam sensors particularly suitable for applications involving significant deformations.

[0067] In order to evaluate the sensing performance of TPU / CNT@PDA / AgNWs foam strain sensor, as Fig.12 As shown in Figure 2, the relative resistance change curves of TPU / CNT@PDA / AgNWs foams under tensile strains up to 244% were measured. Sensitivity is a key parameter of sensors, reflecting their ability to detect changes in external stress, which are usually quantified by their GF. In the strain range of 0%-244%, the sensitivity of the sensor increases significantly with strain: GF 1 2.64 at 70% strain, GF 2 Increased to 7.49 at 140% strain, GF3 It reaches 9.32 at 244% strain, showing excellent strain sensing performance. Through cyclic tests at 5%, 10%, 20%, 30% and 40% strain, Fig.13 It was further confirmed that the resistance increased steadily with increasing strain, indicating excellent repeatability and linear response in a small strain range. Figure 14-15 The response and recovery times of the sensor are shown, both measured at 40ms, highlighting the fast response capability of the sensor. Fig.16 The results of 4000 cycles of tensile testing at 20% strain are shown, where the SDs for the first and last 20 cycles are 0.193% and 0.181%, respectively. The inset further confirms the stability and predictability of the resistance variation trend during the cyclic test.

[0068] The heating performance of TPU / CNT@PDA / AgNWs foam was systematically evaluated and the change of its temperature coefficient of resistance (TCR) with increasing temperature from 20°C to 100°C was studied. Fig.17 The conduction mechanism in TPU / CNT@PDA / AgNWs foam is consistent with a thermally activated process, where carrier mobility increases with increasing temperature, thereby increasing resistance. The resistance change of TPU / CNT@PDA / AgNWs foam over multiple cycles between 20°C and 70°C shows high reproducibility and stability ( Fig.18 ). These results demonstrate not only the excellent thermal stability and TCR (temperature coefficient of resistance) of the TPU / CNT@PDA / AgNWs foam, but also its outstanding sensitivity to temperature changes. These properties provide valuable insights for the future development of smart sensors and thermal monitoring systems.

[0069] Example 2

[0070] First, TPU particles are dissolved in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 25%, and the solution is stirred at 55°C for 18 hours to ensure that the TPU / DMF solution is uniform; 2% (carboxylated carbon nanotube CNT powder is gradually added to the solution, and the solution is stirred at 55°C for 18 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 50%; the mixed solution is poured into a glass culture dish and dried in an oven at 85°C overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

[0071] The TPU particles are dissolved in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 25%, and the solution is stirred at 55°C for 18 hours to ensure that the TPU / DMF solution is uniform; 2% (carboxylated carbon nanotube CNT powder is gradually added to the solution, and the solution is stirred at 55°C for 18 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template agent, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 50%; the mixed solution is poured into a glass culture dish and dried in an oven at 80°C overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

[0072] Mix 15 mL of ethylene glycol (EG) and 10.5 mg of copper chloride dihydrate (CuCl 2 ·2H 2 Prepare two beakers containing 45 mL of EG, add 1413 mg of polyvinyl pyrrolidone (PVP) to one beaker and 718.5 mg of silver nitrate (AgNO 3 All the solutions were ultrasonically treated in a 25°C water bath until completely dissolved; then 150 mL of EG solution was placed in a 500 mL three-necked flask and refluxed at 160°C for 2.5 hours; then, 1200 μL of CuCl dissolved by ultrasonication was added. 2 ·2H 2 O solution was slowly added to the reaction system, and the addition process lasted for about 10-20 minutes; then, 45 mL of PVP solution was gradually added; after the above reaction was completed, AgNO 3 -EG solution was added to the reaction system in stages, and the addition time was controlled within 17 minutes; the reaction temperature was maintained at 160°C, and the reaction was continued for 3 hours; after the reaction, the solution was cooled to room temperature, and 4 volumes of acetone were added to complete the precipitation; the final product was washed 4 times with acetone and anhydrous ethanol, and centrifuged at 6000 rpm for 7 minutes to remove residual impurities; the product was dispersed in deionized water and prepared into a 3 mg / mL AgNWs solution.

[0073] Prepare a dopamine solution by preparing a 15 mM Tris-HCl buffer (pH 8.5) and dissolving dopamine; immerse the obtained TPU / CNT foam in the dopamine solution and stir the reaction at room temperature for 18 hours to achieve uniform polymerization of surface dopamine; after the reaction is completed, rinse the foam with deionized water to remove unpolymerized dopamine monomers; place the dopamine-modified foam in a vacuum drying oven and dry it at 60°C for 18 hours to ensure the stable formation of the surface dopamine film, and finally obtain a PDA-modified TPU / CNT composite material.

[0074] The obtained TPU / CNT@PDA composite material was immersed in AgNWs dispersion (concentration of 3 mg / mL) and gently stirred at room temperature for 45 minutes to allow AgNWs to evenly adhere to the foam surface; the AgNWs-impregnated TPU / CNT@PDA foam was repeatedly immersed in the AgNWs dispersion, and the load of AgNWs was recorded to obtain the TPU / CNT@PDA composite material; copper foil electrodes were connected at both ends of the TPU / CNT@PDA composite material, and the upper and lower surfaces of the TPU / CNT@PDA composite material were respectively encapsulated with PI film, and then wires were led out from the copper foil electrodes at both ends to assemble the TPU / CNT@PDA / AgNWs foam strain sensor.

[0075] Example 3

[0076] First, TPU particles are dissolved in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 30%, and the solution is stirred at 60°C for 24 hours to ensure that the TPU / DMF solution is uniform; 3% (carboxylated carbon nanotube CNT powder is gradually added to the solution, and the solution is stirred at 60°C for 24 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 80%; the mixed solution is poured into a glass culture dish and dried in an oven at 90°C overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which are immersed in warm water and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

[0077] The TPU particles are dissolved in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 30%, and the solution is stirred at 60°C for 24 hours to ensure that the TPU / DMF solution is uniform; 3% (carboxylated carbon nanotube CNT powder is gradually added to the solution, and the solution is stirred at 60°C for 24 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template agent, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 80%; the mixed solution is poured into a glass culture dish and dried in an oven at 90°C overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

[0078] First, 20 mL of ethylene glycol (EG) and 14 mg of copper chloride dihydrate (CuCl 2 ·2H 2 Prepare two beakers containing 60 mL of EG, add 1884 mg of polyvinyl pyrrolidone (PVP) to one beaker and 958 mg of silver nitrate (AgNO 3 All the solutions were ultrasonically treated in a 30°C water bath until completely dissolved; then 200 mL of EG solution was placed in a 500 mL three-necked flask and refluxed at 170°C for 3 hours; then, 1600 μL of CuCl dissolved by ultrasonication was added. 2 ·2H 2 O solution was slowly added dropwise to the reaction system for about 20 minutes. Then, 60 mL of PVP solution was gradually added. After the above reaction was completed, AgNO 3 -EG solution was added to the reaction system in stages, and the addition time was controlled within 120 minutes; the reaction temperature was maintained at 170°C, and the reaction was continued for 4 hours; after the reaction, the solution was cooled to room temperature, and 5 volumes of acetone were added to complete the precipitation; the final product was washed with acetone and anhydrous ethanol 5 times, and centrifuged at 7000 rpm for 10 minutes to remove residual impurities; the product was dispersed in deionized water and prepared into a AgNWs solution with a concentration of 4 mg / mL.

[0079] Prepare a dopamine solution by preparing a 20 mM Tris-HCl buffer (pH 8.5) and dissolving dopamine; immerse the obtained TPU / CNT foam in the dopamine solution and stir the reaction at room temperature for 24 hours to achieve uniform polymerization of surface dopamine; after the reaction is completed, rinse the foam with deionized water to remove unpolymerized dopamine monomers; place the dopamine-modified foam in a vacuum drying oven and dry it at 70°C for 24 hours to ensure the stable formation of the surface dopamine film, and finally obtain a PDA-modified TPU / CNT composite material.

[0080] The obtained TPU / CNT@PDA composite material was immersed in AgNWs dispersion (concentration of 4 mg / mL) and gently stirred for 60 minutes at room temperature to allow AgNWs to evenly adhere to the foam surface; the AgNWs-impregnated TPU / CNT@PDA foam was repeatedly immersed in AgNWs dispersion, and the load of AgNWs was recorded to obtain the TPU / CNT@PDA composite material; copper foil electrodes were connected at both ends of the TPU / CNT@PDA composite material, and the upper and lower surfaces of the TPU / CNT@PDA composite material were respectively encapsulated with PI film, and then wires were led out from the copper foil electrodes at both ends to assemble the TPU / CNT@PDA / AgNWs foam strain sensor.

Claims

1. A method for preparing a TPU / CNT@PDA / AgNWs foam strain sensor, characterized in that: The following steps are involved: Step 1, preparing TPU / CNT composite foam; Step 2, preparation of AgNWs dispersion; Step 3, preparation of TPU / CNT@PDA / AgNWs foam strain sensor; Step 3.1, PDA modification of TPU / CNT foam; Step 3.2, dip-loading of AgNWs.

2. The method for preparing a TPU / CNT@PDA / AgNWs foam strain sensor according to claim 1, characterized in that: Step 1 is implemented according to the following steps: Dissolve TPU particles in dimethylformamide (DMF) to prepare a TPU solution with a mass fraction of 20-30%, and stir at 50-60°C for 12-24 hours to ensure that the TPU / DMF solution is uniform; 1-3% carboxylated carbon nanotube CNT powder is gradually added to the above solution, and stirring is continued at 50-60° C. for 12-24 hours to form a uniformly dispersed TPU / DMF / CNT mixed solution; NaCl particles are added to the mixed solution as a template, and the mixture is stirred evenly to ensure that the NaCl particles are evenly distributed, and the foaming rate of the mixture is adjusted to 20-80%; the mixed solution is poured into a glass culture dish, and dried in an oven at 70-90° C. overnight to volatilize the DMF solvent; the dried composite foam material still contains NaCl particles, which is immersed in warm water, and the NaCl template particles are completely removed through multiple immersion cycles; after the NaCl particles are removed, the obtained material is washed and dried to finally obtain a TPU / CNT composite foam.

3. The method for preparing a TPU / CNT@PDA / AgNWs foam strain sensor according to claim 1, characterized in that: Step 3.1 is implemented as follows: Prepare a dopamine solution by preparing a 10-20 mM Tris-HCl buffer (pH 8.5) and dissolving dopamine; immerse the TPU / CNT foam obtained in step 1 in the dopamine solution and stir the reaction at room temperature for 12-24 hours to achieve uniform polymerization of surface dopamine; after the reaction is completed, rinse the foam with deionized water to remove unpolymerized dopamine monomers; place the dopamine-modified foam in a vacuum drying oven and dry it at 50-70° C. for 12-24 hours to ensure the stable formation of the surface dopamine film, and finally obtain a PDA-modified TPU / CNT composite material.

4. The method for preparing a TPU / CNT@PDA / AgNWs foam strain sensor according to claim 3, characterized in that: Step 3.2 is implemented as follows: The TPU / CNT@PDA composite material obtained in step 3.1 is immersed in the AgNWs dispersion (concentration of 2-4 mg / mL) obtained in step 2, and gently stirred for 30-60 minutes at room temperature to allow the AgNWs to evenly adhere to the foam surface; and the AgNWs-impregnated TPU / CNT@PDA foam is repeatedly immersed in the AgNWs dispersion, and the load of the AgNWs is recorded to obtain the TPU / CNT@PDA composite material; copper foil electrodes are connected at both ends of the TPU / CNT@PDA composite material, and the upper and lower surfaces of the TPU / CNT@PDA composite material are respectively encapsulated with PI (polyimide) films, and then wires are led out from the copper foil electrodes at both ends to assemble the TPU / CNT@PDA / AgNWs foam strain sensor.

5. A TPU / CNT@PDA / AgNWs foam strain sensor, characterized in that: The method is prepared by any one of claims 1 to 4.